The quenching of indolic compounds by monosubstituted benzenes and the photoreaction with chlorobenzene - Rivarola, Claudia Rosana (2003)
The quenching of the excited singlet of indole and its methyl derivatives by monosubstituted benzenes has been studied in three solvents of different polarities and bimolecular quenching rate constants have been determined. Below the diffusion limit the rate constants decrease when solvent polarity increases, with the exception of those for the quenching by benzonitrile. For the latter the rate constants are near the diffusion limit in all cases. The decrease may be understood in terms of a lower energy of the indole excited state in the more polar solvents. In cyclohexane the remnant emission in the presence of high concentration of the quencher is clearly red shifted, indicating the presence of a new emitting species that can be ascribed to the presence of an exciplex. In some cases the emission of the exciplex can be clearly separated from the molecular fluorescence. In the quenching by chlorobenzene in ethyl acetate and acetonitrile a new highly fluorescent product is formed. This photoreaction is observed with all the indole derivatives and the kinetics of the reaction was followed by the increase in fluorescence intensity at a wavelength were the reactants do not emit. Three major products were identified as phenyl substituted indoles by GC-MS and their fluorescence emission and excitation spectra.